Urban ventilation of typical residential streets and impact of building form variation. (April 2021) - Peng, Yunlong; Gao, Zhi; Buccolieri, Riccardo; Shen, Jialei; Ding, Wowo
Highlights: The ventilation of residential streets is analysed. Several building form variations in Nanjing are considered. Two orientations of streets are investigated: North-South and East-West. Bended buildings improve the ventilation of East-West oriented streets. Street perpendicular buildings improve the ventilation of North-South oriented streets. Abstract: This paper numerically investigates the ventilation of residential streets bounded by buildings of different forms. The aim is to provide suggestions for the design of environmentally sustainable urban streets in residential areas. Four representative building form variations along residential streets in Nanjing, located in the Yangtze River Delta region in China, i.e. 'rotation', 'stagger', 'bend' and 'annex building', are considered and several idealized models are finally built for the ventilation analysis. The focus is on the most common East-West (EW) and North-South (NS) oriented streets subjected to parallel, perpendicular and inclined wind directions. Results show that, for the investigated wind directions, NS oriented streets experience a better ventilation than EW oriented streets for all wind directions. For EW oriented streets, it is suggested to avoid buildings parallel to the street to prevent poor street ventilation conditions, while bended buildings are found to improve the ventilation. For NS oriented streets, keeping the buildings perpendicular to the street as much as possible is the most effective way to improve the street ventilation. Moreover, the presence of annex buildings, employed for commercial purposes, although reduces the airpath between buildings, for a given wind direction has little effect on street ventilation.